Phylogenomics and phylogeography of Menispermum (Menispermaceae) - Song, Shiqiang; Cameron, Kenneth M.; Wang, Yuguo; Wang, Shenyi; Jin, Xinjie; Hina, Faiza; Yang, Zhaoping; Li, Pan (Frontiers in Plant Science, 2023)
Phylogenomics have been widely used to resolve ambiguous and controversial evolutionary relationships among plant species and genera, and the identification of unique indels in plastomes may even help to understand the evolution of some plant families. Menispermum L. (Menispermaceae) consists of three species, M. dauricum DC., M. canadense L., and M. mexicanum Rose, which are disjunctively distributed among East Asia, Eastern North America and Mexico. Taxonomists continue to debate whether M. mexicanum is a distinct species, a variety of M. dauricum, or simply a synonym of M. canadense. To date, no molecular systematics studies have included this doubtful species in phylogenetic analyses. In this study, we examined phylogenomics and phylogeography of Menispermum across its entire range using 29 whole plastomes of Menispermaceae and 18 ITS1&ITS2 sequences of Menispermeae. We reconstructed interspecific relationships of Menispermum and explored plastome evolution in Menispermaceae, revealing several genomic hotspot regions for the family. Phylogenetic and network analyses based on whole plastome and ITS1&ITS2 sequences show that Menispermum clusters into two clades with high support values, Clade A (M. dauricum) and Clade B (M. canadense + M. mexicanum). However, M. mexicanum is nested within M. canadense and, as a result, we propose that M. mexicanum is a synonym of M. canadense. We also identified important molecular variations in the plastomes of Menispermaceae. Several indels and consequently premature terminations of genes occur in Menispermaceae. A total of 54 regions were identified as the most highly variable plastome regions, with nucleotide diversity (Pi) values > 0.05, including two coding genes (matK, ycf1), four introns (trnK intron, rpl16 intron, rps16 intron, ndhA intron), and 48 intergenic spacer (IGS) regions. Of these, four informative hotspot regions (trnH-psbA, ndhF-rpl32, trnK-rps16, and trnP-psaJ) should be especially useful for future studies of phylogeny, phylogeography and conservation genetics of Menispermaceae.